Investigating Dark Energy Equation of State With High Redshift Hubble Diagram - Demianski, Marek; Lusso, Elisabeta; Paolillo, Maurizio; Piedipalumbo, Ester; Risaliti, Guido (Frontiers in Astronomy and Space Sciences, 2020)
Several different data sets revealed the accelerated expansion rate of the Universe, usually assumed to be driven by the so called dark energy, which, according to recent estimates, provides about 70% of the total amount of matter-energy in the Universe. The nature of dark energy is yet unknown. Several models of dark energy have been proposed: a non zero cosmological constant, a potential energy of some self interacting scalar field, effects related to the non homogeneous distribution of matter, or effects due to alternative theories of gravity. A tension between predictions of the flat ΛCDM model and a high-redshift Hubble diagram (HD) of supernovae, and quasars has been discovered in [1, 2], and it has been confirmed in [3] adding a gamma-ray bursts HD. Here we use the same data performing a statistical analysis in order to constraint the dark energy EOS. Our high redshift HD supports indication (at > 3σ level) of an evolving dark energy EOS, thus confirming the previous results.